Strategi peningkatan Pemanfaatan Perpustakaan di Perpustakaan Khusus Sekretariat DPRD Provinsi Sumatera Barat - Mayora, Hilda; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purpose of this research were to (1) describe the factors that led to the lack of visits a librarian at DPRD’s library of Province Sumatera Barat, (2) explain how to exact used strategy in the use of libraries as a means of information provider at DPRD’s library of Province Sumatera Barat. Data were collected through observation and interviews with librarian at DPRD’s library of Province Sumatera Barat. Analysis data was collected used description. In this study have two factors that are led to the lack of the advantages of library and the strategy that usefull for solve the problem at DPRD’s library of province of Sumatera Barat. The suggestion that can be delivered in this articles are, (1) the library of DPRD Province of Sumatera Barat must be think about the strategy or the way to increase the advantages of the library for librarian, (2) wish that librarian can be creative to increase the library function, (3) for staff it can give more attantion for library. Keywords: strategy; library; information; libraries